Foraging range, habitat use and minimum flight distances of East Atlantic Light-bellied Brent Geese Branta bernicla hrota in their spring staging areas - Clausen, Kevin K.; Clausen, Preben; Hounisen, Jens P.; Vissing, Marie S.; Fox, Anthony D. (Wildfowl, 2013)
Global Positioning System (GPS) satellite telemetry was used to determine the foraging range, habitat use and minimum flight distances for individual East Atlantic Light-bellied Brent Geese Branta bernicla hrota at two spring staging areas in Denmark. Foraging ranges (mean Â± s.d. = 53.0 Â± 23.4 km2) were comparatively large, greater than reported elsewhere for this species, and habitat use revealed a high exploitation of salt marshes (64.4%), which now replace traditional fjord habitats as the most important for spring-fattening. At one site (AgerÃ¸), geese had started to exploit agricultural fields (winter-sown cereals; 11.8% of the total GPS location data), and in all areas fjords were still frequently used for roosting at night. Minimum flight distances for foraging excursions at the staging sites varied considerably between individual geese (ranging from 4.64â€“10.14 km/day), and these were related to differences in habitat use. Geese using a high proportion of agricultural areas flew greater distances than those avoiding this habitat. Compared to historical data on the same population, these findings indicate a significant enlargement of foraging ranges and increased use of terrestrial habitats. This might reflect changes in habitat availability, and is probably related to significant declines in Common Eelgrass ZosteraÂ marina in both these areas. From a historically rather sedentary lifestyle, which centred around foraging on Zostera beds in fjord habitats, this population now feeds onÂ scattered areas of salt marsh, and increasingly on inland winter-sown cereals, in a progressively cultivated landscape. As fjord habitats remain the preferred roosting areas (probably as a consequence of differences in perceived habitat-specific predation risk), this â€œterrestrialisationâ€ of Brent Goose habitat use is associated with increased energetic costs in the form of higher minimum flight distances.